Efficacy and Safety of Silodosin and Dutasteride Combination Therapy in Acute Urinary Retention due to Benign Prostatic Hyperplasia: A Single-Arm Prospective Study. (18th April 2016) - Hagiwara, Kazuhisa; Koie, Takuya; Iwamura, Hiromichi; Imai, Atsushi; Hatakeyama, Shingo; Yoneyama, Takahiro; Hashimoto, Yasuhiro; Ohyama, Chikara
Abstract : This study aimed to assess the efficacy of combination therapy with dutasteride and silodosin in patients with acute urinary retention (AUR) caused by benign prostatic hyperplasia (BPH). Eighty consecutive patients with a first episode of AUR were enrolled in this study. All patients received silodosin 8 mg and dutasteride 0.5 mg daily. Trial without catheter (TWOC) was attempted every 2 weeks until 12 weeks after the initiation of medication. The primary endpoint was the rate of catheter-free status at 12 weeks. Voided volume (VV), postvoid residual urine (PVR), uroflowmetry, International Prostatic Symptoms Score (IPSS), and quality of life due to urinary symptoms (IPSS-QOL) were also measured. All patients were followed up for more than 12 weeks and were included in this analysis. The success rate of TWOC at 12 weeks was 88.8%. VV and maximum urinary flow rate were significantly higher at 2, 4, 8, and 12 weeks compared with the time of AUR (P < 0.001 ). IPSS and IPSS-QOL were significantly lower at 2, 4, 8, and 12 weeks compared with the time of AUR (P < 0.001 ). In conclusion, a combination of dutasteride and silodosin therapy may be effective and safe for patients with AUR due to BPH.